Response of biofertilizer and urea on growth and yield in mungbean - Mondal, Mohd Monjurul Alam; Malek, Mohammad Abdul; Sattar, M. A.; Puteh, Adam; Yusop, Mohd Rafii; Ismail, Mohd Razi (Agricultural Research Communication Centre, 2013)
The effect of biofertilizer and urea on growth parameters, yield and yield attributes of two mungbean varieties was investigated. Application of biofertilizer and urea was more effective in promoting plant growth and yield attributes than sole application of biofertilizer or urea. Among the fertilizer combinations, biofertilizer with recommended TSP, MP, gypsum and one-third urea exhibited superiority in plant height, number of branches plant−1, leaf area plant−1, number of nodules plant−1, chlorophyll content in leaves, total dry mass plant−1, absolute growth rate, number of pods plant−1, harvest index and seed yield as compared to other fertilizer treatments. Therefore, biofertilizer with 13 kg urea ha−1 may be recommended for increasing seed yield of mungbean.